IMPROVING THE TECHNIQUE OF BADMINTON SPORTS TRAINING - Shermatov, G’ulom (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article discusses various strategies and techniques to improve badminton sports training. It covers a range of aspects including technical skills, physical conditioning, mental preparation, and tactical awareness. The article emphasizes the importance of individualized training, match analysis, and incorporating drills that simulate game situations. It also highlights the significance of proper rest and recovery, injury prevention, and continuous learning. The aim is to provide badminton players with valuable insights and practical guidance to enhance their overall technique and performance on the court.